2012
DOI: 10.1002/ejlt.201200106
|View full text |Cite
|
Sign up to set email alerts
|

Altering the scissile fatty acid binding site of Candida antarctica lipase A by protein engineering for the selective hydrolysis of medium chain fatty acids

Abstract: Candida antarctica lipase A (CAL‐A) is the first representative of a new subclass of lipases because of its unique cap domain. The acyl‐binding tunnel – having a short alternative binding region – is mainly formed by this domain. In order to create CAL‐A variants with a high specificity for medium chain length (MCL) fatty acids (C6–C12), we used rational protein design to block the primary acyl‐binding tunnel of CAL‐A at position G237, which is near the junction to the alternative binding pocket. By closing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Analogous results were reported by Schmitt et al [15]. Recently, Brundiek et al [49] reported that mutant G237A/L/V/Y altered the substrate specificity of Candida antarctica lipase A by interrupting 19 the acyl-binding tunnel. Zhou et al [50] reported that M148W substitution of meta-cleavage product hydrolase could interrupt the tunnel T2.…”
Section: Discussionsupporting
confidence: 75%
“…Analogous results were reported by Schmitt et al [15]. Recently, Brundiek et al [49] reported that mutant G237A/L/V/Y altered the substrate specificity of Candida antarctica lipase A by interrupting 19 the acyl-binding tunnel. Zhou et al [50] reported that M148W substitution of meta-cleavage product hydrolase could interrupt the tunnel T2.…”
Section: Discussionsupporting
confidence: 75%
“…It has previously been shown that modifying the size, physico‐chemical properties and dynamics of access tunnels by protein engineering can change the catalytic activity, substrate specificity, enantioselectivity and stability of HLDs8, 33, 54–56 and many other enzymes with buried active sites57 such as cytochrome P450s,58–63 β‐glucosidases,64 lipases,15, 6569 esterases70 and epoxide hydrolases 47. 71, 72…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the unique construction of the acyl tunnel of lipase A determines a perfect fit for long-chain fatty acids and also affects the selectivity towards trans -fatty acids (Brundiek et al 2012). …”
Section: Resultsmentioning
confidence: 99%